Voluntary adoption of the International Standards on Auditing (ISA) in local government audits—empirical evidence from Finland. Issue 3 (3rd April 2023) - Rönkkö, Jaakko; Lilja, Mikko; Oulasvirta, Lasse
IMPACT: This article will be useful to policy-makers and public sector managers in terms of understanding how public audit regulation affects audit practitioners in determining applicable audit standards. Over 70% of chartered public finance auditors in Finland were found to voluntarily adopt the International Standards on Auditing (ISA) despite a regulatory environment where the ISA were not strictly required in local government audits.